Heavy Metal Bioaccumulation, Growth Characteristics, and Yield of Pisum sativum L. Grown in Agricultural Soil-Sewage Sludge Mixtures - Ebrahem M. Eid; Ahmed F. El-Bebany; Mostafa A. Taher; Sulaiman A. Alrumman; Tarek M. Galal; Kamal H. Shaltout; Nasser A. Sewelam; Mohamed T. Ahmed (Plants, 2020)
The application of sewage sludge (SS) in agriculture is an alternative disposal method for wastewater recycling and soil fertilization. This study evaluated heavy metal bioaccumulation, growth, and yield of Pisum sativum (pea) grown in agricultural soil amended with SS at rates of 0, 10, 20, 30, and 40 g/kg. The results show that root, shoot, pod length, biomass, and number of leaves and pods increased with SS amendments of 10 and 20 g/kg, while rates declined at 30 and 40 g/kg. SS had greater salinity and organic content than the soil. Heavy metals in the postharvest soil samples increased for all SS application rates except Fe and Mo. The significant increase in Cd content started at the lowest amendment rate 10 g/kg; for Co, Mn, and Pb, the significant increase was detected at the highest amendment rate (40 g/kg). Generally, all heavy metals increased significantly in portions of P. sativum except Cd in the shoot. At an amendment rate of 10 g/kg, Co in the shoot and root, Cr in the fruit, Cu in the root, Fe in the fruit, Mn in the shoot and fruit, Mo in the fruit, Pb in the shoot, and Zn in the fruit were elevated significantly. In contrast, the concentrations of Cd in the fruit, Cr in the root, Cu in the shoot, Fe in the shoot and root, Ni in the fruit and root, Pb in the fruit and root, and Zn in the root significantly increased only at the highest rate of 40 g/kg. The highest regression R2 was 0.927 for Mn in pods and the lowest was 0.154 for Cd in shoots. Bioaccumulation and translocation factors were > 1 for Mo and the bioaccumulation of Pb was >1. SS could be used for pea fertilization but only at rates below 20 g/kg to avoid environmental and health hazards.